The process of wealth accumulation with regard to the path dependence theory - Kranzinger, Stefan (Momentum Quarterly, 2016)
This paper analyses the process of wealth accumulation with regard to the path dependence theory. Based on the theoretical foundations of Robert King Merton, Vilfredo Pareto and Pierre Bourdieu, mechanisms of wealth accumulation are analyzed. These mechanisms, which are understood as direct and indirect network effects, are formalized using the statistical computing software R. A base model without any mechanisms of wealth accumulation is developed, which makes it possible to include the analyzed mechanisms step by step and observe their effects on the process of wealth accumulation and social inequality. Piketty’s findings from his work Capital in the 21st Century are included in the formalized models of wealth accumulation, in particular the relationship between the rate of return on capital and the growth rate of the economy.
Keywords: social inequality; wealth accumulation; wealth transmission; path dependence